(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The authors analyze the occurrence of specific complications and the main causes of the complicated course of the early and late period after surgical treatment of GD. The authors conclude that the use of an improved method of surgical access to the thyroid gland and a program of postoperative rehabilitation made it possible to reduce the frequency of specific complications, which in general ensured an increase in the proportion of good and satisfactory results from 90.1% to 98.3% with a decrease in the probability of an unsatisfactory outcome from 17 .3% to 3.0%.